ARE PEER FEEDBACK ACTIVITY ESSENTIAL IN ONLINE ARGUMENTATIVE WRITING? - Elda Yulia Ryandini (Universitas Islam Negeri Alauddin Makassar, 2019)
ABSTRACT: The purposes of this research were to investigate and classify peer feedback activity in online argumentative writing and to probe the essence of getting peer feedback. This research used qualitative approach to respond the research problems. The subjects of this study were 3 students from a writing class of English Education Department at Islamic University in East Java. Data were collected through observation and semi-structured interview. The findings of this research showed that there were various feedback given by peers such as no thesis statement in introduction, short sentences in body and conclusion paragraphs, incomplete ideas in introduction, error grammars and sentence structures, no clear counter arguments and refutations in body paragraphs, no refutation in body paragraph, not cover idea of body paragraph in conclusion, not debatable title, and not confusing position whether agree or disagree with the topic. The result also indicated that the essence of getting peer feedback in online argumentative writing were positive proved by the students’ enthusiastic derived from interview.